Key factors influencing the adoption of e-government in Iran - Shajari, M. (IEEE, 2011)
Compare to developed countries, e-Government implementation in developing countries seems to be slower. One of the important issues for the e-Government services is adoption of users. Finding the factors which impact on the adoption of government e-Services would lead the managers to a better technology adoption model which is more suitable for e-Government. This study presents the essential factors based on the interviews with the IT managers in the public organization using e-Government services. This study uses the most discussed adoption models to identify the factors. Based on interviews done in Iran's public organizations, this study finds the suitable factors and includes trustworthiness as an external key factor influencing the adoption of e-Government services.